Bionic flexible force sensor based on tenon-and-mortise structure and high-performance medical patch

Through bionic flexible force sensors based on mortise and tenon structure and high-performance medical patch materials, the problem of difficulty in force control during the implantation of traditional medical patches is solved, precise implantation and optimized treatment effects are achieved, and the mechanical properties of the materials are improved and drug controlled release capability.

CN119164522APending Publication Date: 2024-12-20GUANGZHOU MEDICAL UNIV
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411366153.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Traditional medical patch (myocardial or skin) materials are difficult to accurately measure and control the applied force during implantation, resulting in complications and affecting the therapeutic effect.

Method used

Using a bionic flexible force sensor based on mortise and tenon structure, combined with high-strength biocompatible materials and adaptive enhancement learning algorithms, multi-axis directional force sensing and data processing are realized, and integrated into the surface or interior of medical patches through microadhesion technology. Ensure precise implantation.

Benefits of technology

It realizes precise control and optimization of the medical patch implantation process, reduces complications, and provides high mechanical properties, conductivity and drug controlled release.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119164522A_ABST
    Figure CN119164522A_ABST
Patent Text Reader

Abstract

The invention provides a bionic flexible force sensor based on a tenon-and-mortise structure and a high-performance medical patch material, belongs to the technical field of biomedical engineering, and can be used for multiple organ tissues such as myocardium and skin. The bionic flexible force sensor is provided with an upper base and a lower base; the upper base and the lower base are of a concave-convex interlocking tenon-and-mortise structure. A plurality of convex tenons are designed on the bottom surface of the upper base, a plurality of concave mortises corresponding to the tenons are designed on the top surface of the lower base, and the tenons and the mortises are precisely matched to form stable locking; the tenons and the mortises are connected through buckle structures, and sliding and loosening are prevented. The bionic flexible force sensor is integrated and fixed on the surface or inside the medical patch through a micro-adhesion technology. A renewable wood-based enhanced visible light 3D printing technology is adopted, and nanofibers, nanocrystals and composite nanoparticles are combined, so that the patch material has excellent mechanical properties, electrical conductivity and drug controlled release property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical engineering, and in particular to a bionic flexible force sensor based on a mortise and tenon structure and a high-performance medical patch material. Background Art

[0002] Medical patch (myocardium) is an engineered heart tissue, which combines seed cells that have the ability to form cardiomyocytes with suitable scaffold materials to construct a biomaterial for repairing or replacing autologous myocardium.

[0003] It is difficult to accurately measure and control the force applied during the implantation of traditional medical patch (myocardial or skin) materials, which may lead to complications and affect the treatment effect. Traditional medical patch (myocardial or skin) surgery cannot directly monitor the implantation process of the medical patch (myocardial or skin); and traditional medical patch (myocardial or skin) materials have poor mechanical properties, conductivity and drug release control.

[0004] To solve this problem, the present invention has developed a bionic flexible force sensor based on the traditional Chinese mortise and tenon structure and a high-performance medical patch (myocardial or skin) material to ensure precise control and effect optimization of the medical patch (myocardial or skin) implantation process. Summary of the invention

[0005] The purpose of the present invention is to solve the problem that it is difficult to accurately measure and control the force applied during the implantation of traditional medical patch (myocardial or skin) materials, which leads to complications and affects the treatment effect, thereby ensuring the precise control of the medical patch (myocardial or skin) implantation process and optimizing the effect.

[0006] To achieve the above object, the present invention provides the following solutions: Bionic flexible force sensor based on mortise and tenon structure, The bionic flexible force sensor has an upper base and a lower base with a mortise and tenon structure, and the base design enables the sensor to more conveniently sense forces in the x, y, and z directions; The upper and lower bases have dimensions of 3 × 3 × 3 mm³, and the bases use a concave-convex interlocking mortise and tenon structure, similar to the connection between myocardial fibers, to ensure that the sensor has good contact and force conduction in multi-axis directions; The bottom surface of the upper base is designed with 4 protruding tenons with a size of 0.8 × 0.8 × 0.8 mm³, and the top surface of the lower base is designed with a concave mortise corresponding to the tenons with a size slightly larger than 0.8 × 0.8 × 0.8 mm³. The tenons and mortise are precisely matched to form a stable locking effect, similar to the tight connection between myocardial cells, which enhances the stability and flexibility of the structure. In the connection method, the tenon and the mortise are connected by a snap-fit ​​structure to prevent sliding and loosening. The snap-fit ​​structure has a height of 0.2 mm and a width of 0.2 mm, which mimics the connection method between cardiomyocytes and ensures high stability and precise force conduction.

[0007] Furthermore, the upper base and the lower base are made of high-strength biocompatible materials, and the biocompatible materials are polylactic acid (PLA) or polycaprolactone (PCL), ensuring that no rejection reaction will be caused in the biological environment. The material selection imitates the elasticity and strength of myocardial tissue.

[0008] Furthermore, the sensor is integrated as follows: a piezoresistive sensing unit is embedded inside the mortise and tenon structure, each unit has a size of 0.2 × 0.2 × 0.2 mm³, and the piezoresistive sensing unit is connected to an external data processing unit via a micro-connecting line to transmit the detected force information in real time; Furthermore, the sensor uses an adaptive reinforcement learning algorithm (AEL) to decode the data of the sensor's piezoresistive sensing unit. AEL combines deep reinforcement learning (DRL) and genetic algorithm (GA) to ensure the accuracy and adaptability of data processing by continuously adjusting weights and strategies.

[0009] As another improvement, the sensor is printed with an upper base and a lower base by a molten 3D printer, and then the piezoelectric sensor with a sandwich structure consisting of a biocarbon electrode layer-HFPD-PVA film-biocarbon electrode layer is embedded and packaged between the upper base and the lower base by a print-pause-sample addition-reprint method to achieve sensor packaging.

[0010] Another technical solution of the present invention is a high-performance medical patch (myocardium or skin) material, including the above-mentioned bionic flexible force sensor, which is integrated and fixed on the surface or inside of the medical patch (myocardium or skin) through micro-adhesion technology to ensure that it will not shift during the implantation process and the bionic myocardial cells are tightly attached.

[0011] Furthermore, the medical patch (myocardial or skin) material is prepared by the following method: S1. Preparation of nanofibers and nanocrystals: Renewable wood-based materials such as wood powder, bamboo powder, straw powder, and cork powder are added to dilute sulfuric acid and 1,2-propylene glycol, 1,3-propylene glycol, and 1,4-butylene glycol / water solvents for ultrasonic chemical treatment to obtain nanofibers and nanocrystals; S2. Preparation of composite nanoparticle micro-nanospheres: In an ethanol / water solvent system, the cellulose and lignin coating structures are self-assembled with composite nanoparticles such as titanium dioxide, zinc oxide, and silicon dioxide to form micro-nanospheres; S3. Microsphere preparation: Microspheres containing specific nanoparticles were prepared using microfluidics and ultrasonic hydrothermal method, including PLGA microspheres, polylactic acid microspheres, polycaprolactone microspheres, gelatin microspheres, and methacrylate polymer microspheres; S4. Photo-cross-linked polymer curing: Using the bio-ink visible light photocuring 3D printing technology, the material prepared in step S1-3 is three-dimensionally visible light cured to form a medical microneedle patch (myocardial or skin) structure. The formed medical patch (myocardial or skin) structure is a bionic conch-shaped microneedle structure.

[0012] Furthermore, the preparation method of the methacrylated gelatin is as follows: Gelatin is used as a raw material, and the gelatin is dissolved in PBS at a ratio of 2-3 g: 20 ml. The gelatin is slowly reacted with methacrylic anhydride, methacrylamide or methyl methacrylate at a volume ratio of 20:3 in the PBS system to replace the hydroxyl groups on the gelatin and introduce acrylic acid groups to prepare methacrylated gelatin. The gelatin is dialyzed for 48-72 hours and vacuum freeze-dried for 12-24 hours, and then purified to obtain high-purity GelMA made of methacrylic anhydride, methacrylamide or methyl methacrylate.

[0013] Compared with the prior art, the present invention has the following technical effects: The sensor is integrated into the medical patch (myocardial or skin) to monitor and measure the magnitude and direction of the force applied during the patch implantation process in real time, providing precise data to help doctors adjust the operation, reduce complications and optimize the treatment effect.

[0014] The sensor can be applied in fields such as smart medical equipment, human monitoring and rehabilitation devices. The ability of the sensor to detect complex multi-axis stimuli provides a new strategy for the design of multi-dimensional force sensors.

[0015] Using renewable wood-based enhanced visible light 3D printing technology, combined with nanofibers, nanocrystals and composite nanoparticles, the patch material has excellent mechanical properties, conductivity and drug controlled release. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] For ease of explanation, the present invention is described in detail with reference to the following specific embodiments and the accompanying drawings.

[0017] Figure 1 This is a schematic diagram of the integration of the bionic flexible force sensor of the present invention.

[0018] Figure 2 It is a flow chart of the present invention.

[0019] Figure 3 These are SEM images of cellulose gels added in different proportions according to the present invention.

[0020] Figure 4This is a diagram of the colchicine loading and release process of the present invention.

[0021] Figure 5 The polarization images and voltage change diagrams of the films at different ratios of the present invention are shown.

[0022] Figure 6 This is the FTIR graph of the cellulose modified and encapsulated material of the present invention.

[0023] Figure 7 This is a performance test diagram of the microneedle material at different scales of the present invention.

[0024] Figure 8 This is a performance test diagram of the microneedle material at different scales of the present invention. DETAILED DESCRIPTION

[0025] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments; in the following description, specific details such as specific configurations are provided only to help fully understand the embodiments of the present invention. Therefore, it should be clear to those skilled in the art that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of the present invention.

[0026] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features of the embodiments may be combined with each other.

[0027] Unless otherwise specified, the materials, practices and experimental equipment involved in the implementation cases of the present invention are all in line with commercially available products in the relevant chemical and biotechnology fields. Example 1

[0028] This embodiment provides a bionic flexible force sensor based on a mortise and tenon structure. The bionic flexible force sensor has an upper base and a lower base with a mortise and tenon structure, and the base design enables the sensor to more conveniently sense forces in the x, y, and z directions; The upper and lower bases have dimensions of 3 × 3 × 3 mm³, and the bases use a concave-convex interlocking mortise and tenon structure, similar to the connection between myocardial fibers, to ensure that the sensor has good contact and force conduction in multi-axis directions; The bottom surface of the upper base is designed with 4 protruding tenons with a size of 0.8 × 0.8 × 0.8 mm³, and the top surface of the lower base is designed with a concave mortise corresponding to the tenons with a size slightly larger than 0.8 × 0.8 × 0.8 mm³. The tenons and mortise are precisely matched to form a stable locking effect, similar to the tight connection between myocardial cells, which enhances the stability and flexibility of the structure. In the connection method, the tenon and the mortise are connected by a snap-fit ​​structure to prevent sliding and loosening. The snap-fit ​​structure has a height of 0.2 mm and a width of 0.2 mm, which mimics the connection method between cardiomyocytes and ensures high stability and precise force conduction.

[0029] Furthermore, the upper base and the lower base are made of high-strength biocompatible materials, such as polylactic acid / polybutylene succinate (PLA / PBS) or polyurethane (TPU), to ensure that no rejection reaction will be caused in the biological environment, and the material selection imitates the elasticity and strength of myocardial tissue.

[0030] Furthermore, the sensor is integrated as follows: a piezoresistive sensing unit is embedded inside the mortise and tenon structure, each unit has a size of 0.2 × 0.2 × 0.2 mm³, and the piezoresistive sensing unit is connected to an external data processing unit via a micro-connecting line to transmit the detected force information in real time; Furthermore, the sensor uses an adaptive reinforcement learning algorithm (AEL) to decode the data of the sensor's piezoresistive sensing unit. AEL combines deep reinforcement learning (DRL) and genetic algorithm (GA) to ensure the accuracy and adaptability of data processing by continuously adjusting weights and strategies.

[0031] Another improvement, such as Figure 1 As shown, the sensor is printed with a 3D printer to print the upper base and the lower base. Specifically, the package (the 3D printed piezoelectric package shown in the figure) is modeled on the CAD software and printed using a 3D printer (FDM). The printing material is PLA-g-MAH (polylactic acid grafted maleic anhydride) mixed with PBS (polybutylene dibutyrate). Then, the biocarbon electrode layer (shown in the figure) is printed by the method of printing-pausing-adding sample-reprinting. + The piezoelectric sensor (i.e., the piezoresistive sensing unit) composed of a sandwich structure of carboxymethyl wood powder)-HFPD-PVA film-biocarbon electrode layer (shown in the figure as -carboxymethyl wood powder) is embedded and packaged into the upper base and the lower base (shown in the figure as the packaging layer) to achieve packaging. Example 2

[0032] This embodiment provides a high-performance medical patch (myocardium or skin) material, including the bionic flexible force sensor described in Example 1, which is integrated and fixed on the surface or inside of the medical patch (myocardium or skin) through micro-adhesion technology to ensure that it will not shift during the implantation process and the bionic myocardial cells are tightly attached.

[0033] Furthermore, the medical patch (myocardial or skin) material is prepared by the following method: S1. Preparation of nanofibers and nanocrystals: Renewable wood-based materials such as wood powder, bamboo powder, straw powder, and cork powder are added to dilute sulfuric acid and 1,2-propylene glycol, 1,3-propylene glycol, and 1,4-butylene glycol / water solvents for ultrasonic chemical treatment to obtain nanofibers and nanocrystals; S2. Preparation of composite nanoparticle micro-nanospheres: In an ethanol / water solvent system, the cellulose and lignin coating structures are self-assembled with composite nanoparticles such as titanium dioxide, zinc oxide, and silicon dioxide to form micro-nanospheres; S3. Microsphere preparation: Microspheres containing specific nanoparticles were prepared using microfluidics and ultrasonic hydrothermal method, including PLGA microspheres, polylactic acid microspheres, polycaprolactone microspheres, gelatin microspheres, and methacrylate polymer microspheres; S4. Photo-cross-linked polymer curing: Using the bio-ink visible light photocuring 3D printing technology, the material prepared in step S1-3 is three-dimensionally visible light cured to form a medical microneedle patch (myocardial or skin) structure. The formed medical patch (myocardial or skin) structure is a bionic conch-shaped microneedle structure.

[0034] In this embodiment, 1. Selection and preparation of microneedle materials: In order to make the material anti-inflammatory, printable, with high mechanical properties and the function of promoting myocardial cell recovery, methacryloyl gelatin (GelMA) was selected as the microneedle substrate, blended with chitosan, nanocellulose, polygallic acid, and loaded with colchicine.

[0035] 1.1 Preparation of methacryloyl gelatin (GelMA): Using gelatin as raw material, 10-15g gelatin was dissolved in 100mL PBS, and then slowly reacted with methacrylic anhydride / methacrylamide / methyl methacrylate (15mL) in the PBS system to replace the hydroxyl groups on the gelatin and introduce acrylic acid groups to prepare methacrylic gelatin (GelMA), which was dialyzed for 48-72h and vacuum freeze-dried for 12-24h before purification to obtain high-purity GelMA made of methacrylic anhydride / methacrylamide / methyl methacrylate. Preliminary experiments have shown that GelMA made of methacrylic anhydride is most suitable as the substrate for this material.

[0036] 1.2 Preparation of Nanocellulose: Using poplar wood powder as raw material, acetic acid, lactic acid and dilute sulfuric acid are used to catalyze the butanediol / water solvent system to separate cellulose with high yield and high purity. The separated cellulose components are further converted into cellulose nanofibers through chemical combined with ultrasonic treatment.

[0037] 1.3 Preparation of polygallic acid: Dissolve 0.1-0.4 g of gallic acid in 35°C pure water (10-40 mL) to form a uniform solution. Adjust the GA solution to 10 with 0.5 g / ml NaOH solution and react for 20-40 minutes to polymerize into polygallic acid.

[0038] 1.4 Preparation of chitosan sol: Dissolve 1~5mL of glacial acetic acid in 50mL of water and add 0.5~2g of chitosan until it is completely dissolved and becomes a jelly.

[0039] 2. Preparation of GelMA hydrogel: 2.1 Preparation of hydrogel solution: Take 2~4mL chitosan jelly, add 160~180μL polygallic acid solution and 0.02~0.08g nanocellulose particles, put in an ice bath, and place in an ultrasonic crusher for 30min to form a uniformly dispersed precursor solution. Take 0.315g freeze-dried GelMA, add 2mL precursor solution, and stir for 30min in a 60-degree water bath to form a GelMA solution to be cross-linked. Add tris(2,2′-bipyridyl) ruthenium (II) chloride hexahydrate (Ru) and sodium persulfate (SPS) composite photoinitiator under light-proof conditions, mix evenly, and completely protect from light to prepare a hydrogel solution with photoinitiator added.

[0040] 2.2 Printing hydrogel microneedles: The designed microneedle structure was modeled on CAD software, imported into slicing software for slicing, and printed using a dedicated volume bioprinter under 450nm light to make hydrogel microneedles.

[0041] 3. Piezoelectric sensor design: 3.1 Preparation of HFPD-PVA piezoelectric film: Take 0.1~0.8g PVA (Mw=98000), add 1mL pure water, and stir for 2h in a 90° water bath to fully dissolve it. Add 1mL 0.2g / mL HFPD solution, stir for 1h at 40° to mix evenly, add to a six-well culture dish with a diameter of 35.53mm, dry at 40° for 24h, and stand at room temperature for 12h to form a HFPD-PVA film.

[0042] 3.2 Preparation of biocarbon electrode: Poplar wood blocks were selected as materials, and NaOH and Na2SO4 solutions were added to soak them at 100 degrees to remove cellulose. After being taken out, 30% hydrogen peroxide solution was used to soak them at 100 degrees for 4 hours to remove lignin. The obtained samples were placed in a tubular furnace, argon was used as a protective gas, the flow rate was 100, the heating rate was 5 degrees per minute, the carbonization temperature was 700 degrees, the duration was 5 minutes, the temperature dropped to room temperature by natural heat dissipation, ground, compacted, and used as biochar electrodes.

[0043] 3.3 Packaging of piezoelectric sensors (such as Figure 1 shown): The package (shown in the figure) was modeled on the CAD software and printed using a fused 3D printer (FDM). The printing material was PLA-g-MAH (polylactic acid grafted maleic anhydride) mixed with PBS (polybutylene dibutyrate). The biocarbon electrode layer (shown in the figure) was printed using the print-pause-add sample-reprint method. + The piezoelectric sensor (i.e., the piezoresistive sensing unit) composed of a sandwich structure of carboxymethyl wood powder)-HFPD-PVA film-biocarbon electrode layer (shown in the figure as -carboxymethyl wood powder) is embedded and packaged into the upper base and the lower base (shown in the figure as the packaging layer) to achieve packaging.

[0044] Microneedle system testing 1. Microneedle structure design Microneedle surface morphology and structural characteristics: Scanning electron microscopy (SEM) was used to detect the surface morphology and structural characteristics of the microneedles.

[0045] like Figure 3 As shown in the figure, the scanning electron microscope (SEM) images of nanocellulose with different concentrations (0.2%, 0.4%, 0.6%, 0.8%) added to a certain matrix material are shown by SEM images, with magnifications of 100X, 500X, 1000X and 2000X respectively. With the increase of nanocellulose addition, the microstructure of the matrix material changed significantly. At an addition of 0.2%, the surface of the matrix material was uniform, without obvious holes or cracks, but small holes began to appear at 500X magnification, and the number of holes increased and the size became larger at 1000X and 2000X magnifications, and the pore walls were relatively smooth and evenly distributed. As the addition amount increased to 0.4%, the holes became more obvious, the pore size was evenly distributed, the internal structure was more complex, and the pore edges were irregular. At 0.6% addition, the pore density increased, the pore size was different, the pore wall thickness decreased, and the pore wall surface became irregular. Finally, at 0.8% addition, the pore density reached the maximum, the pores were connected into a sheet-like structure, the number of pores was the largest and the distribution was uneven, some pores were connected to form a network structure, the internal structure of the pores was very complex, the pore wall surface was rough and more fine structures and cracks appeared. In general, the addition of nanocellulose significantly increased the porosity and surface roughness of the matrix material, and a higher concentration of addition could significantly change the microstructure of the material, which had an important impact on the mechanical properties and functionality of the material (such as drug loading and release characteristics).

[0046] 2. Microneedle penetration and drug loading and release behavior Drug loading and release of drug models: The drug loading and release were observed by UV spectrophotometer to verify the uniformity and effectiveness of drug loading.

[0047] like Figure 4 As shown in the figure, the absorption spectra of colchicine-loaded materials in different wavelength ranges under different strains (100%, 200%, 300%, 400%, 500%), as well as the changing trend of absorption intensity under different strains. In each figure, the horizontal axis represents the wavelength (nm) and the vertical axis represents the absorbance. The red dotted line marks the absorbance value at 353 nm. Under 100% strain, the absorbance of the material at 353nm is 0.6271, and as the strain increases to 200%, the absorbance increases slightly to 0.6366; at 300% strain, the absorbance further increases to 0.6937. At this time, the strain rate of the material is 95.85%. When the strain increases to 400%, the absorbance of the material at 353 nm increases significantly to 0.8277, corresponding to a strain rate of 134.52%. Finally, at 500% strain, the absorbance of the material reaches a maximum value of 0.9452, corresponding to a strain rate of 146.69%.

[0048] The line graph of the drug-loaded material shows the trend of absorbance at 353 nm under different strains, indicating that the absorbance gradually increases with the increase of strain, especially after the strain exceeds 300%, the absorbance increases significantly. This shows that the optical properties of the material have changed significantly during the stretching process, and the increase in absorbance is related to the reorganization of the internal structure of the material or the change in the molecular distance. Since the absorbance is related to the concentration of the drug, the drug loading rate of the material under high strain is improved. This phenomenon is of great significance for studying the optical properties and drug release characteristics of materials under different mechanical strain conditions.

[0049] Piezoelectric sensor testing 1. Piezoelectric performance test at different ratios Piezoelectric coefficient (d33) determination: The piezoelectric coefficient of different HFPD ratios was determined using a piezoelectric measuring device.

[0050] Piezoelectric voltage coefficient (g33) test: The piezoelectric voltage coefficient of different HFPD ratios was measured using an electrochemical workstation.

[0051] 2. Force-dependent and frequency-dependent piezoelectric output voltage at the optimal ratio Force-dependence testing: The piezoelectric output voltage is measured under different applied forces using a mechanical tester to analyze the response of the piezoelectric material to force.

[0052] Frequency dependence test: The piezoelectric output voltage is measured at different frequencies to analyze the response of the piezoelectric material to frequency.

[0053] 3. Electrical stimulation experiment Effect of electric field on cell release: Study the effect of electric field generated by HFPD materials under mechanical stress on cell release. Improve cell release efficiency by optimizing electrical stimulation parameters (such as frequency, amplitude, duration).

[0054] Cell growth and proliferation observation: Cardiomyocytes were cultured on the microneedle system, and the growth, proliferation, and release of cells under electrical stimulation were observed. The effects were evaluated by microscopic observation and biochemical testing.

[0055] like Figure 5 As shown in the figure, polarizing microscope images and microstructural features of PVA and HFPD-PVA nanocomposites at different thicknesses and different processing conditions, as well as piezoelectric response performance under different time and temperature conditions. From the polarizing microscope images, it can be seen that with the increase of HFPD content and thickness, the particle size on the surface of the material increases significantly, indicating that the distribution of nanoparticles becomes more obvious. HFPD-PVA composites of different thicknesses show different surface roughness and particle aggregation, among which samples with higher concentrations and thicknesses show more significant nanostructures and aggregation phenomena. The three-dimensional chart on the right shows the piezoelectric response performance of the material under different time and temperature conditions. The results show that the piezoelectric response intensity fluctuates regularly with time, and there are differences in the piezoelectric response intensity at different temperatures, indicating that the piezoelectric performance of the material under different temperature environments is stable and controllable. These results show that the microstructure and piezoelectric properties of the material can be effectively regulated by adjusting the thickness and HFPD content of the HFPD-PVA composite, providing an experimental basis for further optimization and application of the material.

[0056] Bionic flexible force sensor testing 1. Sensor sensitivity test: Design a bionic flexible force sensor based on HFPD material and test its sensitivity to ensure that it can sense tiny mechanical stress changes.

[0057] 2. Signal processing and data analysis: Analyze sensor data in real time and extract characteristic parameters of heart beats, such as heart rate, waveform, etc. Integrate the sensor with the data processing module and perform preliminary testing and calibration.

[0058] 3. Response surface analysis: The response surface analysis design experimental method was used to determine the optimal levels of factors such as chitosan, nanocellulose, polygallic acid and photoinitiator, and to optimize the preparation conditions of modified lignocellulose nanocrystals.

[0059] like Figure 6As shown, the infrared spectral characteristics of cellulose and packaging materials reflect the infrared transmittance (%) of different samples at different wave numbers (cm⁻¹). The image on the left shows the infrared spectral characteristics of cellulose, which contains many different types of cellulose and its derivatives. The absorption peaks marked in the figure correspond to the characteristic absorption peaks of functional groups such as hydroxyl (-OH), methylene (-CH2), methyl (-CH3), ester group (C=O), vinyl (-C=C-) and ether bond (COC). With the change of different cellulose types, the absorption peak positions and intensities of these functional groups also change, reflecting the diversity of cellulose structure and the influence of chemical modification.

[0060] The image on the right shows the infrared spectra of three encapsulation materials (KMPLA / PBS-2, KPPLA / PBS, MPPLA / PBS). Similar to the spectrum of cellulose, these materials also show characteristic absorption peaks of major functional groups in the corresponding wavenumber range. In particular, the absorption peaks of hydroxyl, methylene, ester and ether bonds clearly show the chemical bonding and structural composition of these encapsulation materials.

[0061] Structure-property correlation study: Use SEM, TEM, FTIR, XRD, XPS and other testing instruments to measure the morphology, structure and chemical composition of the samples, conduct statistical analysis and modeling to determine the optimal preparation conditions.

[0062] like Figure 7 As shown, the experimental data of mechanical properties, rheological properties and surface chemical characteristics of hydrogels with different cellulose content ratios. The upper row of three-dimensional graphs shows the stress-strain relationship, the relationship between compression force and time, and the relationship between compression stress and strain of hydrogels with different cellulose contents. The results show that with the increase of cellulose content, the mechanical strength of the hydrogel is significantly enhanced, showing higher stress and stronger pressure resistance.

[0063] The middle row of figures shows the rheological test results of hydrogels with different cellulose contents, including the changes in storage modulus (G'), loss modulus (G") and complex viscosity (|η*|) with frequency (ω). The results show that with the increase of cellulose content, the storage modulus and loss modulus of the hydrogel increased significantly, indicating that its elasticity and viscosity were enhanced. At the same time, the complex viscosity increased significantly in the low frequency band, indicating that the viscoelastic properties of the hydrogel were significantly improved.

[0064] The bottom row of figures shows the X-ray photoelectron spectroscopy (XPS) spectra of hydrogels with different cellulose contents. The left figure shows the high-resolution XPS spectrum of C 1s, the middle figure shows the high-resolution XPS spectrum of O 1s, and the right figure shows the full spectrum of different elements. The XPS results show that with the increase of cellulose content, the characteristic peak intensity of chemical bonds such as CC / CH, COC and OC=O is significantly enhanced, indicating that the introduction of cellulose significantly changes the surface chemical composition of the hydrogel and increases the oxygen content and the ratio of carbon-oxygen bonds.

[0065] Based on these data, it can be concluded that the addition of cellulose significantly improves the mechanical properties and viscoelastic properties of the hydrogel, while also changing its surface chemical characteristics. These results show that by regulating the content of cellulose, the comprehensive properties of the hydrogel can be effectively optimized, giving it a wider application prospect in fields such as biomedical engineering.

[0066] Microneedle performance optimization 1. Multiple regression analysis: Use multiple regression analysis and other statistical methods to establish a mathematical model, and use experimental data to predict the performance of microneedle gel materials.

[0067] 2. Microneedle molding experiment: The molding effect of microneedle bio-ink is expressed through various characterizations.

[0068] like Figure 8 As shown, the experimental data of the contact angle, environmental stability, gloss and color of the hydrogels with different cellulose contents. The left figure in the upper row shows the relationship between the contact angle of the hydrogels with different cellulose contents and time. The results show that with the increase of cellulose content, the contact angle of the hydrogel decreases significantly, indicating that its hydrophilicity is enhanced. The right figure in the upper row shows the performance of the hydrogels with different cellulose additions in terms of environmental stability, including indicators such as processing time, environmental sensitivity, and molding stability. The radar chart shows that the addition of cellulose significantly improves the environmental stability and molding stability of the hydrogel.

[0069] The middle row of figures shows the glossiness of hydrogels with different components. The results show that with the increase of cellulose content, the glossiness of the hydrogel gradually decreases, but still maintains a high level overall, indicating that the addition of cellulose has a certain effect on the optical properties of the hydrogel but it is not significant.

[0070] The lower row of figures shows the color characteristics of hydrogels with different cellulose contents, including color distribution and chromaticity changes. The results show that there are certain differences in the colors of hydrogels with different cellulose contents, but the overall chromaticity distribution is uniform, indicating that the addition of cellulose has a positive effect on the color stability of the hydrogel.

[0071] In summary, these data show that the addition of cellulose can significantly improve the hydrophilicity and environmental stability of hydrogels, and at the same time has a certain optimization effect on their optical properties and color stability. By regulating the content of cellulose, the comprehensive performance of hydrogels can be effectively improved, giving them a wider application prospect in biomedical and engineering applications.

[0072] The mechanical properties test uses tensile and compression testing methods to evaluate the strength, toughness and other mechanical properties of medical patch (myocardial or skin) materials; The conductivity test adopts a four-probe method or other testing methods to measure the conductivity of the medical patch (myocardial or skin) material and evaluate its conductivity; The drug release performance test studies the release rate and controlled release performance of the medical patch (myocardial or skin) material to the drug through an in vitro release experiment.

[0073] In a further embodiment, the applied research is: The myocardial infarction treatment application is to evaluate the myocardial infarction treatment effect in an animal model and observe the effect and safety of the medical patch (myocardial or skin) material in the treatment of myocardial infarction.

[0074] In summary, this bionic flexible force sensor, which combines the traditional Chinese mortise and tenon structure, achieves high-precision, multi-dimensional force detection through ingenious structural design and advanced material selection, and is particularly suitable for the precise implantation and treatment of medical patches (myocardium or skin). Through detailed structural description and size parameters, the present invention ensures the stability, sensitivity and biocompatibility of the sensor, while using the adaptive reinforcement learning algorithm (AEL) to process data to improve the accuracy and adaptability of the sensor. The medical patch (myocardium or skin) material achieves high mechanical properties, conductivity and drug controlled release properties through the innovative combination of nanofibers, nanocrystals and composite nanoparticles, providing new material selection and technical support for the treatment of myocardial infarction.

[0075] Those skilled in the art to which the present application belongs may make various modifications or additions to the specific embodiments described or replace them in a similar manner, but they will not deviate from the inventive concept of the present application or exceed the scope defined by the attached claims.

Claims

1. A bionic flexible force sensor based on a mortise and tenon structure, characterized in that: The bionic flexible force sensor comprises an upper base and a lower base; The upper and lower bases adopt a concave and convex interlocking mortise and tenon structure; The bottom surface of the upper base is designed with a number of protruding tenons, and the top surface of the lower base is designed with a number of recessed mortises corresponding to the tenons. The tenons and mortises are precisely matched to form a stable lock; The tenon and mortise are connected by a snap-fit ​​structure to prevent sliding and loosening.

2. The bionic flexible force sensor based on the mortise and tenon structure according to claim 1 is characterized in that: The upper base and the lower base are made of high-strength biocompatible material, and the biocompatible material is polylactic acid / polybutylene succinate or polyurethane.

3. The bionic flexible force sensor based on the mortise and tenon structure according to claim 2 is characterized in that: The sensor is integrated as follows: A piezoresistive sensing unit is embedded inside the mortise and tenon structure and connected to an external data processing unit via a micro-connecting line to transmit the detected force information in real time.

4. The bionic flexible force sensor based on the mortise and tenon structure according to claim 3 is characterized in that: An adaptive reinforcement learning algorithm is used to decode the data from the sensor's piezoresistive sensing unit.

5. The bionic flexible force sensor based on the mortise and tenon structure according to claim 4 is characterized in that: The dimensions of the upper base and the lower base are 3 × 3 × 3 mm³, the dimension of the tenon is 0.8 × 0.8 × 0.8 mm³, the dimension of the mortise is greater than 0.8 × 0.8 × 0.8 mm³, the height of the snap structure is 0.2 mm, the width is 0.2 mm, and the dimension of the piezoresistive sensing unit is 0.2 × 0.2 × 0.2 mm³.

6. The bionic flexible force sensor based on the mortise and tenon structure according to any one of claims 1 to 5, characterized in that: The upper base and the lower base are printed by a molten 3D printer, and then the piezoelectric sensor with a sandwich structure consisting of a biocarbon electrode layer-HFPD-PVA film-biocarbon electrode layer is embedded and packaged between the upper base and the lower base by using the print-pause-sample addition-reprint method to achieve sensor packaging.

7. High-performance medical patch material, characterized in that: The bionic flexible force sensor is integrated and fixed on the surface or inside of the medical patch through micro-adhesion technology.

8. The medical patch material according to claim 7, characterized in that: Prepared by the following method: S1. Preparation of nanofibers and nanocrystals: Renewable wood-based materials such as wood powder, bamboo powder, straw powder, and cork powder are added to dilute sulfuric acid and 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol / water solvents, and subjected to ultrasonic chemical treatment to obtain nanofibers and nanocrystals; S2. Preparation of composite nanoparticle micro-nanospheres: In an ethanol / water solvent system, the cellulose or lignin coating structure is self-assembled with composite nanoparticles such as titanium dioxide, zinc oxide, and silicon dioxide to form micro-nanospheres; S3. Microsphere preparation: Microspheres containing specific nanoparticles were prepared using microfluidics and ultrasonic hydrothermal method, including PLGA microspheres, polylactic acid microspheres, polycaprolactone microspheres, gelatin microspheres, chitosan microspheres, sodium alginate microspheres, and methacrylate polymer microspheres; S4. Photo-cross-linked polymer curing: Using the bio-ink visible light photocuring 3D printing technology, the material prepared in step S1-3 is three-dimensionally visible light cured to form a medical microneedle patch structure. The formed medical patch structure is a bionic conch-shaped microneedle structure.

9. The medical patch material according to claim 8, characterized in that: Methacryloyl gelatin was used as the microneedle substrate, blended with chitosan, nanocellulose, polygallic acid, and loaded with colchicine.

10. The medical patch material according to claim 9, characterized in that: The preparation method of the methacryloyl gelatin is as follows: Gelatin is used as a raw material, and the gelatin is dissolved in PBS at a ratio of 2-3 g: 20 ml. The gelatin is slowly reacted with methacrylic anhydride, methacrylamide or methyl methacrylate at a volume ratio of 20:3 in the PBS system to replace the hydroxyl groups on the gelatin and introduce acrylic acid groups to prepare methacrylated gelatin. The gelatin is dialyzed for 48-72 hours and vacuum freeze-dried for 12-24 hours, and then purified to obtain high-purity GelMA made of methacrylic anhydride, methacrylamide or methyl methacrylate.

Citation Information

Cited By

  • Biodegradable flexible conductive high-hydrophobicity composite film as well as preparation method and application thereof

    CN121650324A

  • A biodegradable flexible conductive high-hydrophobic composite film and a preparation method and application thereof

    CN121650324B

  • Ionic flexible pressure sensor based on bionic gradient tenon-and-mortise structure

    CN121829829A